2022
DOI: 10.3390/diagnostics12123080
|View full text |Cite
|
Sign up to set email alerts
|

Role of Salivary Biomarkers in Diagnosis and Detection of Dental Caries: A Systematic Review

Abstract: Saliva plays a significant role in oral health and tooth integrity. Salivary components reduce tooth surface exposure to demineralization, protect against teeth wear and aid in enamel remineralization. There is a growing attempt to use salivary markers in diagnosing or predicting caries. However, despite the current information, there has yet to be an agreement among scholars. This study seeks to contribute more evidence on the suitability of salivary biomarkers in dental caries diagnosis. Eligible studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Furthermore, saliva plays a crucial role in preventing dental caries (Alamoudi, Alamoudi et al 2022). Systemic and local in ammation can cause structural changes in salivary glands through the action of lymphocytes and in ammatory cytokines, such as CRP, leading to decreased saliva production-a known risk factor for dental caries (Bhattarai, Junjappa et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, saliva plays a crucial role in preventing dental caries (Alamoudi, Alamoudi et al 2022). Systemic and local in ammation can cause structural changes in salivary glands through the action of lymphocytes and in ammatory cytokines, such as CRP, leading to decreased saliva production-a known risk factor for dental caries (Bhattarai, Junjappa et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The total protein content of saliva increases in diabetic patients, oral cancer patients, and patients with history of dental caries. 29 C reactive protein, an inflammatory marker, decreased in saliva after periodontal therapy, suggesting that it could be used as an inflammatory marker. Salivary amylase and total protein content are elevated in leukaemia patients' saliva and can thus be used as a markers too.…”
Section: Discussionmentioning
confidence: 99%
“…A thorough analysis of salivary biomarkers for caries detection revealed that salivary albumin affects dental plaque inflammation and disease severity. Furthermore, salivary albumin levels are negatively correlated with dental caries, with lower levels resulting in more caries ( Alamoudi et al, 2022 ). However, cross-sectional research on 13–19-year-olds found no difference ( Rafieian Kupaei et al, 2013 ).…”
Section: Serum and Salivary Albumin Tests In Recent Oral Health-relat...mentioning
confidence: 99%